An Analysis of Amber Heard's Statements in the Johnny Depp Defamation Case: A Forensic Linguistics Study - Gizela Intania Maylida; Khristianto Khristianto (Journey: Journal of English Language and Pedagogy, 2024)
A defamatory act is any act of speech that disparages the reputation of a person. Defamation is committed by conveying speech in the form of a series of words or sentences by accusing a person of certain actions, which are aimed at honor and good name so that it can result in the person's dignity or dignity being humiliated or degraded. This research aims to examine Amber Heard's statements for defaming Johnny Depp. The data analyzed are Amber Heard's several statements that indicates false and defamatory (primary data) and also her testimony during the trial as supporting data (secondary data). The primary data was collected and observed through the articles op-ed which written by Amber Heard in Washington Post and the secondary data was collected through the trial transcript. This study uses a qualitative research method that describes data to determine the elements that can defame a person based on forensic linguistic studies. By using this study, the data that has been selected was analyzed using lexical semantics, pragmatics (speech acts), and linked to legislation based on Virginia Law. The researchers found three statements that proved to be defamatory and acted with obvious malice that have damaged Johnny Depp's reputation. The findings of this study have significant implications, showing that defamatory statements can have a profound and lasting impact on an individual's reputation and public perception, emphasizing the importance of the law in protecting and addressing such acts.